2013
DOI: 10.1021/ja311180x
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Active Cell-Penetrating Peptides for in Vivo Tumor-Targeted Drug Delivery

Abstract: Cell-penetrating peptides (CPPs) such as transactivator of transcription (TAT) peptide have long been explored for promoting in vitro cell penetration and nuclear targeting of various cargos, but their positive charges cause strong nonspecific interactions, making them inapplicable for many in vivo applications. In this work, we used TAT to demonstrate a molecular modification approach for inhibiting nonspecific interactions of CPPs in the bloodstream while reactivating their functions in the targeted tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
230
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(231 citation statements)
references
References 52 publications
(53 reference statements)
0
230
1
Order By: Relevance
“…Histological analysis of heart tissues showed that the RGDK-FLPP/TRAIL-treated group had compact cardiomyocytes arranged in a clear structure similar to normal tissue, but those of the DOX treated group were characterized by myocardium tissue necrosis and disorganized myofi brillar arrays, typical of cardiomyocyte damage induced by DOX ( Figure S24, Supporting Information). [ 33 ] We have demonstrated a charge-reversal polymer B-PDEAEA which is strongly positively charged and effectively packages DNA into nanoparticles but becomes negatively charged once triggered by intracellular ROS. The resulting ROS-responsive polyplexes show higher gene transfection effi ciency than the traditional gold standard.…”
Section: Communicationmentioning
confidence: 97%
“…Histological analysis of heart tissues showed that the RGDK-FLPP/TRAIL-treated group had compact cardiomyocytes arranged in a clear structure similar to normal tissue, but those of the DOX treated group were characterized by myocardium tissue necrosis and disorganized myofi brillar arrays, typical of cardiomyocyte damage induced by DOX ( Figure S24, Supporting Information). [ 33 ] We have demonstrated a charge-reversal polymer B-PDEAEA which is strongly positively charged and effectively packages DNA into nanoparticles but becomes negatively charged once triggered by intracellular ROS. The resulting ROS-responsive polyplexes show higher gene transfection effi ciency than the traditional gold standard.…”
Section: Communicationmentioning
confidence: 97%
“…A majority of the MP FITC -PEG Cy5.5 -FA NPs DiI was accumulated in the cytoplasm of tumor cells, possibly indicating the localization of the MP-PEG-FA NPs in the endo/lysosomes. 26 However, the drug accumulated in the cytoplasm and nucleus, which was possibly due to the fact that some drug was diffused out (released) from the MP-PEG-FA NPs, distributed through the cytoplasm, and transported inside the cells. 25 A high nuclear drug accumulation also resulted in the rapid drug diffusion to the cytoplasm.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…The PAMAM dendrimer system was modified by conjugating HIV transactivator of transcription (TAT) as cell penetrating peptide to enhance the uptake of the constructed DNA plasmid pIRES-H5/GFP by the cells. Cell-penetrating peptides (CPPs) are highly cationic peptides usually rich in arginine and lysine amino acids and have the ability to translocate quickly into almost any live cells (20).…”
Section: Discussionmentioning
confidence: 99%